181k views
0 votes
8.5b−3.4∙(13a−3.2b)+a

User Riley
by
5.0k points

2 Answers

1 vote

Answer:

8.5b - 3.4(13a - 3.2b) + a = 19.4b - 43.2a

Explanation:

8.5b - 3.4(13a - 3.2b) + a

= 8.5b - 3.4*13a -3.4*(-3.2b) + a

= 8.5b - 3.4*13a + 3.4*3.2b + a

= 8.5b - 44.2a + 10.88 b + a

Now, only like terms can be added to each other

= (8.5b + 10.9b) + (a - 44.2a)

= 19.4b + (-43.2a)

= 19.4b - 43.2a

User Mpmeyer
by
4.7k points
2 votes

Answer:

8.5b - 3.4(13a - 3.2b) + a = 19.4b - 43.2a

Explanation:

It is a simple mathematical problem with multiple like terms. We can solve it by applying basic mathematical rules of multiplication and addition/subtration.

8.5b - 3.4(13a - 3.2b) + a

= 8.5b - 3.4*13a -3.4*(-3.2b) + a

= 8.5b - 3.4*13a + 3.4*3.2b + a

= 8.5b - 44.2a + 10.88 b + a

Now, only like terms can be added to each other

= (8.5b + 10.9b) + (a - 44.2a)

= 19.4b + (-43.2a)

= 19.4b - 43.2a

User Amiasato
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.